An Investigation into the Design of Interdisciplinary Theme-based Learning in Junior Middle School Music under the Perspective of the New Curriculum Standard—Take "Voices of the Yao People: The Intersection of Music and Culture" for Example - Huang, Nan; Li, Jiangtao (Journal of Theory and Practice in Humanities and Social Sciences, 2024)
The 2022 version of the Compulsory Education Curriculum Programme puts forward the requirement of setting up interdisciplinary thematic learning, and the curriculum standard of each discipline includes the relevant requirements including disciplinary synthesis, diversified teaching methods and diversified evaluation mechanisms according to the characteristics of the discipline, etc. This paper discusses the design of interdisciplinary theme learning in junior middle school music under the new curriculum standard, for example, the "Voice of the Yao people: the mingling of music and culture. This paper discusses the design of interdisciplinary theme learning in junior high school music under the new curriculum. Through a series of teaching activities, it demonstrates how to integrate the knowledge of language, history and geography with music as the main subject in order to cultivate students' cultural comprehension and other comprehensive literacy required by the new curriculum. At the same time, the teaching case emphasises the principles of student-centredness, knowledge integration, practical application, diversified assessment and teacher collaboration, aiming to enhance students' critical thinking, teamwork and creativity through interdisciplinary thematic learning, and laying the foundation for their all-round development.